2020
DOI: 10.1136/bmjopen-2019-034666
|View full text |Cite
|
Sign up to set email alerts
|

Results dissemination of registered clinical trials across Polish academic institutions: a cross-sectional analysis

Abstract: ObjectivesTo establish the rates of publication and reporting of results for interventional clinical trials across Polish academic medical centres (AMCs) completed between 2009 and 2013. We aim also to compare the publication and reporting success between adult and paediatric trials.DesignCross-sectional study.SettingAMCs in Poland.ParticipantsAMCs with interventional trials registered on ClinicalTrials.gov.Main outcome measureResults reporting on ClinicalTrials.gov and publishing via journal publication.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Therefore, future analyses of COVID-19 publication productivity should ideally include publications in the Chinese language to obtain a more comprehensive view on this topic. Likewise, many future trials are not yet registered in the WHO database and it has been reported that up to 50% of registered studies are published with a latency of several years and some even remain unpublished [20,21]. Ultimately, our results cover just a four month period and 30 countries.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, future analyses of COVID-19 publication productivity should ideally include publications in the Chinese language to obtain a more comprehensive view on this topic. Likewise, many future trials are not yet registered in the WHO database and it has been reported that up to 50% of registered studies are published with a latency of several years and some even remain unpublished [20,21]. Ultimately, our results cover just a four month period and 30 countries.…”
Section: Discussionmentioning
confidence: 92%
“…Our study protocol and a detailed methods supplement ( https:// osf.io/ 98j7u/ ) allows the replication of our study also for other countries. A first replication based on the study protocol for our former study is already available for Poland [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The datasets and methods used in this study can be scaled: This has been demonstrated in another European country (Poland) [ 48 ] and is currently underway in California, USA [ 49 ]. While the generation of the underlying dataset of clinical trials and associated results publications involves manual checks (approximately 10 person-hours per 100 trials), the assessment of transparency practices is largely automated.…”
Section: Discussionmentioning
confidence: 99%